Factors Influencing Treatment-Seeking Behavior Among Caregivers of Children with Cancer: A Scoping Review - Nurhidayah I; Hendriyani D; Adistie F; Nurhaeni N; Mediani HS (Journal of Multidisciplinary Healthcare)
Ikeu Nurhidayah,1 Desy Hendriyani,2 Fanny Adistie,1 Nani Nurhaeni,3 Henny Suzana Mediani1 1Pediatric Nursing Department, Faculty of Nursing, Universitas Padjadjaran, Sumedang, West Java, 45363, Indonesia; 2Post Graduate Program, Faculty of Nursing, Universitas Padjadjaran, Sumedang, West Java, 45363, Indonesia; 3Pediatric Nursing Department, Faculty of Nursing, Universitas Indonesia, Depok, West Java, 16424, IndonesiaCorrespondence: Ikeu Nurhidayah, Pediatric Nursing Department, Faculty of Nursing, Universitas Padjadjaran. Jl. Raya Bandung-Sumedang, KM. 21, Jatinangor, Sumedang, West Java, 45363, Indonesia, Fax +62 (022) 7795596, Email ikeu.nurhidayah@unpad.ac.idBackground: The survival rates for children with cancer, particularly in developing countries, remain low. A key factor contributing to these poor survival rates is the late diagnosis of pediatric cancer, which is often due to insufficient treatment-seeking behaviors by parents. This study aimed to explore the factors that influence the treatment-seeking behavior among caregivers of children with cancer.Methods: This study employed a scoping review approach. Data was gathered from three sources: PubMed, CINAHL, and Medline. The search protocol adhered to the PRISMA guidelines for scoping reviews, using the terms (“children OR childhood”) AND (“cancer OR malignancy”) AND (“factors OR causes”) AND (“health-seeking behavior OR treatment-seeking behavior”) AND (“treatment delay”). Selected studies were based on original research, utilized either a cross-sectional or qualitative approach, focused on caregivers of children diagnosed with cancer, and were published in the last ten years (2013– 2023).Results: A total of nine articles met the criteria for inclusion: seven were cross-sectional studies, while two were qualitative studies. The ages of the children ranged from 1 to 18 years. Caregivers included parents (mother, father, or both), uncles, siblings, and cousins. The number of respondents varied from 12 to 200. The findings of the studies indicate that a range of complex and interrelated factors affects parental behavior, which includes child-related factors, parent-related factors, knowledge-related factors, perception-related factors, access to health services, and levels of social support.Conclusion: This study highlights that caregiver behavior in seeking treatment for children with cancer is influenced by various factors that all contribute to delays in the treatment. We advocate for increased health promotion initiatives by the government and policymakers aimed at enhancing parents’ knowledge and awareness regarding childhood cancer and its early detection. Expanding the cancer service network in developing countries could improve public access to pediatric cancer services.Keywords: children, factors, cancer, treatment delayed, health-seeking behavior